A gênese, o desenvolvimento e a difusão da folkcomunicação - Amphilo, Maria Isabel (2010)
Research on the genesis of Folkcommunication theory, aiming to identify its epistemological matrices and methodological roots, as well as to characterize its interdisciplinary nature, gravitating around the communication and cultural sciences. The study starts from the analysis of the development of Luiz Beltrão's concepts, contextualizing its initial anchorage in the theory of journalism (1967) and its subsequent expansion to include the dimensions of the social process of communication (1980). Based on the exegesis of the seminal work of the founder of Folkcommunication, we seek to extract the author's contributions to the advancement of communication theories by adapting dimensions of bilaterality and forms of expression of popular culture in communication processes. We also carried out a critical analysis of the theoretical advances and methodological strategies constructed by the scholars who continued the studies of Luiz Beltrão. Then, we investigated the dissemination of knowledge about folkcommunication in Brazil and in the international academic environment. The corpus analyzed was the work of Beltrão on the subject, as well as dissertations, theses, books, articles and scientific communications, which deal with folkcommunication. The methodology used will be based on bibliographic and documental research and taxonomic analysis. The period analyzed will comprise the studies published on Folkcommunication since the original work of Beltrão, in 1967 until 2007.(AU)